Preparation and characterization of loaded paraquat- polymeric chitosan/xantan/tripolyphosphate nanocapsules and evaluation for controlled release - Ghaderpoori, Mansour (J Environ Health Sci Eng, 2020)
PURPOSE: Paraquat is an effective, non-selective, and fast-acting contact herbicide that is widely used. Its high solubility in water and adsorption in soil can easily poison the non-target organs. In this study, paraquat nano-hydrogels was synthesized using chitosan, METHODS: Sodium tripolyphosphate and xanthan via iononic gellification method. After preparation the loaded paraquat formulations, to verify the morphology and analysis the functional groups on the formulation, SEM and FTIR analysis were used, respectively. In this work, stability of the formulation was measured in terms of size distribution, surface charge, and pH values. To determine the release kinetics, a dialysis bag was used. In addition, herbicidal activity of the prepared formulation was tested on corn bushes and wild mustard. RESULTS: From the analysis, FT-IR spectra confirmed the hydrogel formation, and SEM images showed a dense structure in the synthesized hydrogel. According to the results of size distribution, surface charge, dispersion index and pH, it was proved that the prepared hydrogel was stable. The optimal values of chitosan, SPP, xanthan, and PQ were 0.3, 0.1, 0.15, and 20 mg, respectively. Based on the peppas equation, about 89.82% of the paraquat was released from the formulation with a paraquat loading of 89.1 ± 4.6%. CONCLUSIONS: The effect of loaded paraquat formulations on mustard and corn plants showed that the herbicidal properties of the encapsulated paraquat were preserved. This study reveal that the loaded paraquat L-PQ is a stable formulation with less toxicity effects.